Investigation of football players belief, superstition and different behavior tendencies - Rafet Fatih Çakmak; Yücel Ocak (Revista Brasileira de Futsal e Futebol)
Today, it has been observed that athletes in many sports branches show different behaviors. These behaviors increase the mental motivation of the athletes and provide positive contributions to their performance. We aimed to determine the shape and frequency of beliefs, superstitions and different behavioral tendencies of football players before and during training, competition. 60 professional football players in TFF leagues participated in the research. Superstitious Belief and Behavior Inventory in Sports which was developed by Buhramn et al (1982), originally named ‘’Superstitious Ritual Questionnaire’’ and adapted into Turkish by Barut (2008) was used to measure superstitious behaviour. SPSS package program was used for the statistical evaluation of the obtained data. Comparisons between groups were made and the relationships between some variables and behavior patterns were examined. Significance levels were determined as 0.05 and 0.01. As a result,  professional football players have religious behaviors, superstitions and different behavioral tendencies before and during training, competition.